PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT INDOFOOD CBP SUKSES MAKMUR TBK. PERIODE 2013-2022 - Rama Darmawan Iswanto; Martono Martono (CV. ALIM'SPUBLISHING, 2024)
. The purpose of this research was to determine the influence of liquidity and solvency on profitability at PT Indofood CBP Sukses Makmur Tbk. period 2013–2022. This type of research uses the Associative Quantitative method. The research method used in this research uses statistical tests which include multiple linear regression tests and classical assumptions. In the classic SPSS assumptions used by researchers, namely normality, multicollinearity, autocorrelation and heteroscedasticity tests. Partially the author uses the t test, while simultaneously the author uses the F test which is then continued by using the coefficient of determination test. Based on the results of the t test research, it states that Liquidity as proxied by Current Ratio has a negative and significant effect on Profitability as proxied by Return On Assets with t calculated as tcount < ttable, namely |-5.189| > t table 2.364 with a significance level of 0.001 <0.05. And for Sovitability which is proxied by Debt to Asset Ratio, it partially has a negative and significant influence on Profitability which is proxied by Return On Assets because the calculated t value > t table is -19.438 > t table 2.364 with a significance level of 0.000 < 0.05. For the F test, the Fcount value was 197.526> 4.46 with a significance value of 0.000 < 0.05, which means that there is a significant influence simultaneously between Liquidity which is proxied by the Current Ratio and solvency which is proxied by the Debt to Asset Ratio on Provitability which is proxied by Return On Assets in PT Indofood CBP Sukses Makmur Tbk. The resulting coefficient of determination was 98.3% while the remaining 1.7% was the influence of other factors not examined in the author's research.